Influence of Acculturation on Emotional Learning and Memory in Spanish and English Speakers. (30th August 2019) - Zink, D N; Kuwabara, H; Reyes, E; Gomez-Batista, S; Reyes, A; Alvarez, E; Strauss, G P; Allen, D N
Abstract: Objective: The Emotional Verbal Learning Test-Spanish (EVLT-S) is a novel list learning test similar in structure to traditional verbal memory tests but contains words from 4 discrete emotional categories. Influence of acculturation on emotional learning was examined on EVLT-S learning trials 1 to 5. Participants and Method: Participants included 50 bilingual healthy individuals in the Spanish-dominant group (Age M = 20.3years; 72% female) and 27 in the English-dominant group (Age M = 23.4years, 51.9% female). They were administered a battery of tests including the EVLT, a non-emotional verbal list learning test (LLT), Vocabulary (VC), Digit Span (DS), and The Short Acculturation Scale for Hispanics (SASH) in their dominant language. To examine learning curves a mixed model ANOVA was conducted with test (EVLT-S/EVLT, LLT-S/LLT) and trial as within-subjects variables and group (Spanish, English) as a between-subjects variable. Results: There were significant main effects (p < .005) for test, trial, and group. The Spanish-dominant group had the lowest overall performance on the EVLT-S (main effect for group). Post hoc comparisons of the Spanish-dominant group's LLT-S and EVLT-S performance indicated significant differences at each trail (p < .01), with the EVLT-S scores being lower than the LLT-S scores. The ANOVA was repeated with VC, DS, and SASH included as covariates. When controlling for these variables, the main effect for group was no longer significant. A significant trial by acculturation interaction effect emerged (p<.05), with the English-dominant group generally performing better than the Spanish-dominant group. Conclusions: Results suggest that Spanish and English language group differences were largely accounted for by word knowledge (VC), working memory (DS), and acculturation differences (SASH) between the groups. The role of these variables is discussed further in the context of acculturation.